Immobilization of magnetic iron oxide nanoparticles on laponite discs - an easy way to biocompatible ferrofluids and ferrogels - Tzitzios, Vassilios; Basina, Georgia; Bakandritsos, Aristides; Hadjipanayis, Costas G; Mao, Hui; Niarchos, Dimitrios; Hadjipanayis, George C; Tucek, Jiri; Zboril, Radek (Journal of materials chemistry, 2010)
Magnetic nanocomposites containing iron oxide (maghemite) nanoparticles, well embedded in a synthetic clay matrix (laponite) were prepared by a new one step chemical route and characterized by TEM, XRD, magnetization measurements, Mössbauer spectroscopy, DLS, and MRI measurements. The synthetic procedure leads to non-stoichiometric γ-Fe(2)O(3) with a controllable content in the nanocomposite. Magnetic nanoparticles incorporated in the diamagnetic clay matrix exhibit a mean diameter of 13 nm, superparamagnetic behavior with a high saturation magnetization achievable at low applied magnetic fields. In-field Mössbauer spectra and ZFC/FC magnetization curves reveal a perfect ferrimagnetic ordering within nanoparticles with negligible spin frustration and interparticle interactions due to the complete coating of maghemite surfaces by the nanocrystalline laponite matrix. Magnetic iron oxide nanoparticles embedded in laponite matrix exhibit strong T(2) weighted MRI contrast. The maghemite/laponite composite particles have 200 nm hydrodynamic diameter and form very stable hydrosols and/or hydrogels depending on their concentration in water.